Altered Expression of a Malate-Permeable Anion Channel, OsALMT4, Disrupts Mineral Nutrition . Issue 4 (3rd November 2017) - Liu, Jie; Zhou, Meixue; Delhaize, Emmanuel; Ryan, Peter R.
Abstract : Increased expression of a malate-permeable anion channel induced malate release from cells, which altered malate and Mn compartmentation in rice leaves leading to increased sensitivity to Mn. Abstract: Aluminum-activated malate transporters (ALMTs) form a family of anion channels in plants, but little is known about most of its members. This study examined the function of OsALMT4 from rice ( Oryza sativa ). We show that OsALMT4 is expressed in roots and shoots and that the OsALMT4 protein localizes to the plasma membrane. Transgenic rice lines overexpressing (OX) OsALMT4 released malate from the roots constitutively and had 2-fold higher malate concentrations in the xylem sap than nulls, indicating greater concentrations of malate in the apoplast. OX lines developed brown necrotic spots on the leaves that did not appear on nulls. These symptoms were not associated with altered concentrations of any mineral element in the leaves, although the OX lines had higher concentrations of Mn and B in their grain compared with nulls. While total leaf Mn concentrations were not different between the OX and null lines, Mn concentrations in the apoplast were greater in the OX plants. The OX lines also displayed increased expression of Mn transporters and were more sensitive to Mn toxicity than null plants. We showed that the growth of wild-type rice was unaffected by 100 µm Mn in hydroponics but, when combined with 1 mm malate, this concentration inhibited growth. We conclude that increasing OsALMT4 expression affected malate efflux and compartmentation within the tissues, which increased Mn concentrations in the apoplast of leaves and induced the toxicity symptoms. This study reveals new links between malate transport and mineral nutrition.